The contribution of online gaming in Engineering education - Drakatos, Nikolaos; Tsompou, Eleni; Karabatzaki, Zoe; Driga, Anna Maria (Eximia, 2023)
The motivational force that is attributed to games in general is primarily responsible for the rise in popularity of games as educational tools. The study looks at the function that various types of motivation play in educational gaming as well as how the context of the game and the lesson plan affects students’ desire to participate in game play. According to our research, numerous motivational forms can coexist among students who play games, and the interaction between game attractiveness, game learning, and game operativeness can help to explain how these motivational forms evolve. The use of video games in higher education is expanding in the engineering field. The need for virtual labs and technologically advanced experiential learning aids like digital games is anticipated to increase as a result of the new COVID-19 regulations and the shift to virtual learning. An analysis of current techniques in digital game-based learning for engineering education is presented in this research. The most significant benefit is that it offers understanding into how digital game-based learning is applied across many engineering specialties. It also gives scholars and practitioners information about pertinent publications, conferences, games accessible, study designs, and evaluation techniques used in the area of digital game-based learning for engineering. The review’s findings point to an increase in the study on games’ distribution and, maybe, the application of games in engineering education.